Dot immunoperoxidase assay for detection of parvovirus B19 antigens in serum samples. - Gentilomi, G (1997)
We describe a simple and rapid dot immunoperoxidase assay for the direct detection of parvovirus B19 capsid antigens in human sera. The assay was performed with serum specimens dotted onto nylon membranes. VP1 and VP2 B19 antigens, which represent 4 and 96% of the capsid, respectively, were detected with a pool of monoclonal antibodies directed against the two proteins, and the complex was visualized by immunoperoxidase staining. The assay could be performed in about 4 h, and positive results were revealed at the end of the reaction as dark blue spots on the nylon membrane at the site of positive specimens. A total of 541 serum samples from different subjects and with different laboratory evaluations with regard to B19 infection were analyzed. The results obtained by the dot immunoperoxidase assay were compared with the results obtained for the presence of B19 DNA by dot blot hybridization and nested PCR. With optimized working conditions, the dot immunoperoxidase assay was able to detect the presence of B19 with a sensitivity comparable or slightly higher than that achieved by dot blot hybridization but less than that achieved by nested PCR. Since the level of sensitivity of the dot immunoperoxidase assay proved to be appropriate for the detection of acute B19 infection, and since the cost, time to a result, and versatility of the assay are important issues, from our evaluation, the dot immunoperoxidase assay described may be particularly suitable for large-scale screening of samples and a good alternative to DNA detection methods in the routine laboratory evaluation of B19 infection.